2008
DOI: 10.2139/ssrn.1798806
|View full text |Cite
|
Sign up to set email alerts
|

Customer Value-Based Management: Competitive Implications

Abstract: Many …rms today quantify the value of individual customers and serve them di¤erentially; providing better priviliges, discounts or other inducements to high value customers. We refer to this practice as Customer Value-based Management (CVM). Previous research in this area and popular press recommend numerous prescriptions that are research-based and intuitively sound. However, …rms that have adopted CVM have often met with mixed results. For example, only a third of leading U.S. retail banks indicate that they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Although that piece of advice has become widely accepted in recent years as companies have sought to manage their relationships with customers in more sophisticated ways for a clear-cut rationale -firing bad customers might be unhealthy for firms: The notion that "firing unprofitable customers" is a smart thing to do, has emerged out of the broad acceptance of a practice of CRM, where firms often used information technology to quantify the value of individual customers in order to provide better privileges or other inducements to customers identified as having high-value. In their study, Subramanian, Raju and Zhang (2007) added value to the mix and came up with CVM in order to enhance the need for moving CRM to the next level. These customer analyses have often shown that a small proportion of customers contributed to a large percentage of profits, and that many customers were actually unprofitable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although that piece of advice has become widely accepted in recent years as companies have sought to manage their relationships with customers in more sophisticated ways for a clear-cut rationale -firing bad customers might be unhealthy for firms: The notion that "firing unprofitable customers" is a smart thing to do, has emerged out of the broad acceptance of a practice of CRM, where firms often used information technology to quantify the value of individual customers in order to provide better privileges or other inducements to customers identified as having high-value. In their study, Subramanian, Raju and Zhang (2007) added value to the mix and came up with CVM in order to enhance the need for moving CRM to the next level. These customer analyses have often shown that a small proportion of customers contributed to a large percentage of profits, and that many customers were actually unprofitable.…”
Section: Discussionmentioning
confidence: 99%
“…Citing Fidelity Investments were lowvalue customers are made to wait longer in queues to have their calls taken by call centres, they argued that financial institutions were best known for treating low-value customers differently from good ones. However, while acknowledging that firing bad customers may make some sense in industries where there is little or no competition, Subramanian, Raju and Zhang (2007) make it clear that:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors rather focus on the profitability of individual customers and state that "many firms today quantify the value of individual customers and serve them differentially; providing better privileges, discounts or other inducements to high value customers" (Subramanian, Raju and Zhang, 2007).…”
Section: Introductionmentioning
confidence: 99%